Fumonisin B1 induced compositional modifications of the renal and hepatic membrane lipids in rats – Dose and exposure time dependence. Issue 11 (2nd November 2019) - Szabó, András; Fébel, Hedvig; Ali, Omeralfaroug; Kovács, Melinda
ABSTRACT: Male Wistar rats were intraperitoneally dosed with fumonisin B1 (FB1 ; 0, 20, 50 and 100 mg kg −1 dietary dose equivalent) for 5 & 10 days to assess dose- and time-dependent effects on renal and hepatic phosphatidylcholine (PC), phosphatidylinositol (PI) and phosphatidylethanolamine (PE) fatty acid (FA) profiles. Renal PC showed increasing FA saturation (SAT) after 5 days; after 10 days polyunsaturation (PUFA) decreased markedly (Σ n3 (total n3), Σ n6, PUFA, unsaturation index (UI) and average FA chain length (ACL)), mostly with linear dose response. In the PI FAs similar changes were observed, decreasing monounsaturated FA, PUFA, UI and ACL (5 & 10 days), while the PE fraction was responsive in Σ n6 (↓) and SAT (↑), but only after 5 days (without dose response for both PI & PE). Liver PC exhibited increasing saturation (C16:0), decreasing polyunsaturation (C20:3 n6 [dihomo-γ-linolenic acid, DGLA]; C20:3 n3); the PI FA profile showed similar alterations after 5 days. PC & PI FA failed to respond in a dose-dependent manner to FB1 . In PE FA profile DGLA decreased, with a decrease of the total n6 FA proportion and dose-dependent increase of n3 FAs. Results revealed expressed renal sensitivity, supporting our earlier published results in terms of oxidative stress and histopathological modifications.